Two new species of Haploporus (Polyporales, Basidiomycota) from China and Ecuador based on morphology and phylogeny - Man, Xiao-Wu; Dai, Yu-Cheng; Bian, Lu-Sen; Zhou, Meng; Zhao, Heng; Vlasák, Josef (Frontiers in Cellular and Infection Microbiology, 2023)
At present, 25 species are accepted in Haploporus and are distributed in Asia, Europe, North America, South America, Australia, and Africa. In this study, two new species, Haploporus ecuadorensis from Ecuador and H. monomitica from China, are described and illustrated based on morphological examination and phylogenetic analyses. H. ecuadorensis is characterized by annual, resupinate basidiomata with pinkish buff to honey yellow hymenophore when dry, round to angular pores of 2–4 per mm, a dimitic hyphal structure with generative hyphae bearing clamp connections, hyphae at dissepiment edge usually with one or two simple septa, the presence of dendrohyphidia and cystidioles, and oblong to ellipsoid basidiospores measuring 14.9–17.9 × 6.9–8.8 µm. Haploporus monomitica differs from other Haploporus species in that it has a monomitic hyphal system and strongly dextrinoid basidiospores. The differences between the new species and morphologically similar and phylogenetically related species are discussed. In addition, an updated key to 27 species of Haploporus is provided.